Outcome of Covid-19 Related ARDS Patients at a Tertiary Care Hospital - Hafiz Muhammad Rizwan, Shazia Mehmood, Abdul Salam, Saira Sadaf, Arsalan Ahmad Khan Durrani, Muhammad Mohsin Farooq (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In covid-19 related ARDS patients, early approach to proper health care facility and non-invasive ventilation lead to better outcome. Objective: To determine the outcome of covid-19 related ARDS patients at a tertiary care hospital, Rahim Yar Khan. Methodology: This retrospective study was carried out at department of ICU & anesthesiology in collaboration with department of Pulmonology, Sheikh Zayed Medical College/Hospital, Rahim Yar Khan. A total of 74 (confirmed positive PCR) covid-19 ARDS patients with age of 18-90 years of either sex were admitted in covid ICU from June – December 2020. Patients with negative PCR for covid-19 or who presented in gasping condition or received dead were excluded from the study. Outcomes were labelled as recovered (survivors) or died (non-survivors) and treatment outcome was observed in both groups those who were on non-invasive ventilation (NIV) and on invasive mechanical ventilation (IMV). Data was analyzed by using SPSS version 23.0 Results: Out of 74 patients, 60 (81.08%) were male and 14 (18.02%) were female. Middle and old age patients were more affected as compared to young age group (p-value 0.01) and more than half 41 (55.40%) patients went in to severe ARDS. Regarding treatment outcome 44 (59.5%) patients received NIV and 30 (40.5%) patients received IMV. Survival rate better (35.4%) among the patients on NIV as compared to those on IMV (6.7%) respectively. Conclusion: Survival was better among the covid-19 ARDS patients who received NIV as compared to those on IMV. Keeping an eye on respiratory rate and SpO2 is the main factor for the early recognition of ARDS development and severity.